Civilizing habits women missionaries and the revival of French empire - Curtis, Sarah Ann (Oxford University Press, 2010)
This work explores the life stories of three French women missionaries - Philippine Duchesne, Emilie de Vialar, and Anne-Marie Javouhey - who transgressed boundaries, both real and imagined, to evangelize far from France's shores.